Assessments on the Performance of Asphalt Mixtures Prepared with Adhesion Promoters - Nge, Jia Sheng; Mohd Rosli, Mohd Hasan; Sharvin, Poovaneshvaran; Putra Jaya, Ramadhansyah; Ali Huddin, Ibrahim (Blue Eyes Intelligence Engineering & Sciences Publication, 2019)
Asphalt pavement is typically susceptible to moisture damage. However, it could be improved with the incorporation of additives or modifiers through binder modifications. The objective of the study is to assess the effect of adhesion promoters, namely PBL and M5000, onto the Hot Mix Asphalt (HMA). The performance of asphalt mixture has been assessed in terms of the service characteristics, the bonding properties, and mechanical performances. The service characteristics were assessed through the Workability Index (WI) and Compaction Energy Index (CEI) to evaluate the ease of asphalt mixture during the mixing and compaction stage. The bonding properties of the modified asphalt mixtures were determined using the boiling water test and static water immersion test to signify the degree of coating after undergoing specific conditioning period and temperature. The mechanical performances of the modified asphalt mixture were evaluated via Marshall stability, semi-circular bending, and modified Lottman tests. All specimens were prepared by incorporating adhesion promoters at the dosage rates of 0.5% and 1.0% by weight of asphalt binder. From the investigation, the bonding properties significantly improved for the modified asphalt mixture compared to the control mixture. The WI of the modified asphalt mixture increased while the CEI decreased in comparison to the control specimen. This implies the workability of modified asphalt mixture is better and requires less energy to be compacted. Modified asphalt mixture generally had better mechanical performance. Therefore, it can be deduced that the asphalt mixture with adhesion promoters have better overall performance than the control mixture.